Identifikasi Penerapan Pembelajaran Mitigasi Bencana di TK Pembina Kabupaten Gorontalo - Talango, Sitti Rahmawati; Pratiwi, Wiwik; Utina, Sitriah Salim (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Disaster mitigation needs to be introduced in early childhood education institutions.This study was motivated the high disaster risk in Gorontalo Regency, while disaster preparedness education in early childhood centers remains incomplete. This qualitative research aims to identify disaster mitigation learning at TK Pembina Limboto, located in Limboto Village, Gorontalo Regency. The study involved eight teachers as participants. Data were collected through in-depth interviews and analyzed using an interpretative phenomenological approach, grouping statements based on teachers’ experiences, perceptions, and reflections, while also considering the social-emotional context.The findings reveal that disaster mitigation learning at TK Pembina Limboto only covers the pre-disaster and during-disaster phases, focusing on prevention and self-rescue. Teachers have never received disaster preparedness training, so their understanding is limited to basic concepts. However, the simulation based learning applied in the school has shaped teachers’ perception that disaster learning is an important risk reduction effort, as reflected in the emotional responses of children and parents.The implications of this study highlight the need for disaster training for early childhood teachers, the provision of safe school facilities in accordance with Ministry of Education and Culture Regulation No. 33 of 2019, and the integration of a disaster mitigation curriculum that includes pre-disaster, during-disaster, and post-disaster phases. These steps are expected to strengthen the school’s role as an agent of disaster risk reduction.